Aluminium alloy wagon axle box: experience of development, production and operational tests (1958–1993) and modern prospects - A. V. Lapa; I. S. Gershman; S. V. Novikov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Solutions to car weight-bearing capacity problems currently tend to benefit from the properties of aluminium alloys. Aluminium alloy wagon units are about three times lighter than steel ones, which helps to carry more freight with the same number of cars while maintaining the specified axle load. The Ural Wagon Factory was the first to use aluminium as a structural material for the manufacture of axle box mount in the 1950s.Materials and methods. This paper reviews the research on the production of wagon wheel pair axle boxes from aluminium alloys in Russia and abroad. It examines the manufacturing techniques of the aluminium axle box and the results of bench and operational tests.Results. The analysis of production technologies of aluminium alloy axle boxes and the results of operational tests of the pilot batch of axle boxes revealed the advantages and disadvantages of this design and led to the conclusions about its feasibility.Discussion and conclusion. The authors propose to resume the use of aluminium alloys in wagon axle boxes considering modern operating conditions. Confirmation of its technical and economic efficiency requires a set of bench and operational tests with the use of modern diagnostic tools.